Analysis of real-world data and a mouse model indicates that pirfenidone causes pellagra. Issue 4 (24th October 2022) - Kuronuma, Koji; Susai, Natsumi; Kuroita, Tomohiro; Yamamoto, Hiroki; Yoshioka, Takeshi; Kaneko, Shuji; Chiba, Hirofumi
Background: Pirfenidone (PFD) is widely used in patients with idiopathic pulmonary fibrosis (IPF) and its adverse effects, such as nausea and photosensitivity, are well known. Many patients with IPF have reduced doses or even cessation of PFD because of its side-effects. No solutions have been found for these side-effects because the current mechanistic insights are insufficient. Methods: Using the results of real-world data analysis from the US Food and Drug Administration Adverse Events Reporting System, we hypothesised that PFD-related symptoms may be similar to pellagra. Reverse translational experiments using female BALB/c mice were performed to validate and estimate this hypothesis. Niacin and its metabolite responses were compared between patients with IPF treated with PFD and those treated without PFD. Results: The pellagra hypothesis was translated from real-world data analysis. Pharmacological and comprehensive genetic investigations showed that PFD caused pellagra-related nausea and photosensitivity in a mouse model, which may have been mediated by the actions of nicotinamide N- methyltransferase (NNMT). Higher NNMT substrate responses were observed in urine from patients and mice with PFD than in those without PFD. Conclusions: PFD may cause pellagra or pellagra-like symptoms such as photosensitivity. Further studies are required to investigate whether niacin prevents pellagra-like symptoms caused by PFD in patients with IPF. Some adverse effects of pirfenidone (PFD) appear to resemble pellagra but this is the first report to show this phenomenon. Verification is required but side-effects in patients with idiopathic pulmonary fibrosis on PFD may be relieved by niacin. https://bit.ly/3b1kvuR